Efektivitas Konsentrasi HCl Pada Pembuatan Bioetanol Dari Limbah Kulit Nanas - Rosalinda Kolo; Yuni Eka Fajarwati; Susy Yuniningsih (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
Bioethanol is a renewable energy source with significant potential to replace fossil fuels and is widely applied in various industrial sectors. However, bioethanol production in Indonesia still relies heavily on food-based raw materials, raising sustainability and food security concerns. Therefore, the utilization of non-food renewable biomass is essential. Pineapple peel waste is an abundant lignocellulosic by-product that has not been optimally utilized, despite its high carbohydrate content suitable for bioethanol production. This study aimed to evaluate the effect of hydrochloric acid (HCl) concentration during the hydrolysis process on bioethanol production from pineapple peel waste. An experimental method was employed, consisting of raw material preparation, acid hydrolysis using HCl concentrations of 4%, 5%, and 6% at 90°C, fermentation with Saccharomyces cerevisiae for five days, and purification through distillation. The parameters analyzed included ethanol concentration, yield percentage, and pH of the bioethanol product. The results showed that increasing HCl concentration enhanced ethanol concentration, with the highest value of 58.67% obtained at 6% HCl. In contrast, the highest yield (2.87%) was achieved at 4% HCl, while higher acid concentrations led to a decrease in yield, likely due to the formation of inhibitory compounds during hydrolysis. The pH values ranged from 3.4 to 3.8, indicating acidic characteristics. It can be concluded that hydrolysis using 6% HCl at 90°C was the most effective condition for increasing ethanol concentration, although the resulting bioethanol has not yet met the Indonesian National Standard, indicating the need for further optimization.